Defining breakthrough invasive fungal infection–Position paper of the mycoses study group education and research consortium and the European Confederation of Medical Mycology. Issue 9 (19th July 2019) - Cornely, Oliver A.; Hoenigl, Martin; Lass‐Flörl, Cornelia; Chen, Sharon C. ‐A.; Kontoyiannis, Dimitrios P.; Morrissey, C. Orla; Thompson, George R.; ,
Summary: Breakthrough invasive fungal infections (IFIs) have emerged as a significant problem in patients receiving systemic antifungals; however, consensus criteria for defining breakthrough IFI are missing. This position paper establishes broadly applicable definitions of breakthrough IFI for clinical research. Representatives of the Mycoses Study Group Education and Research Consortium (MSG‐ERC) and the European Confederation of Medical Mycology (ECMM) reviewed the relevant English literature for definitions applied and published through 2018. A draft proposal for definitions was developed and circulated to all members of the two organisations for comment and suggestions. The authors addressed comments received and circulated the updated document for approval. Breakthrough IFI was defined as any IFI occurring during exposure to an antifungal drug, including fungi outside the spectrum of activity of an antifungal. The time of breakthrough IFI was defined as the first attributable clinical sign or symptom, mycological finding or radiological feature. The period defining breakthrough IFI depends on pharmacokinetic properties and extends at least until one dosing interval after drug discontinuation. Persistent IFI describes IFI that is unchanged/stable since treatment initiation with ongoing need for antifungal therapy. It is distinct from refractory IFI, defined as progression of disease and therefore similar to non‐response to treatment. Relapsed IFI occurs after treatment and is caused by the same pathogen at the same site, although dissemination can occur. These proposed definitions are intended to support the design of future clinical trials and epidemiological research in clinical mycology, with the ultimate goal of increasing the comparability of clinical trial results.